Ukrainian refugees: Nearly half intend to stay in Germany for the longer term - Herbert Brücker; Andreas Ette; Markus M. Grabka; Yuliya Kosyakova; Wenke Niehues; Nina Rother; C. Katharina Spieß; Sabine Zinn; Martin Bujard; Jean Philippe Décieux; Amrei Maddox; Sophia Schmitz; et al. (DIW Weekly Report, 2023)
Millions of Ukrainians have been displaced by the Russian war on Ukraine, with over one million alone coming to Germany since the beginning of the war. Data from the second survey wave of the IAB-BiB/FReDA-BAMF-SOEP Survey of Ukrainian Refugees in Germany study show that as of the beginning of 2023, an increasing share of Ukrainian refugees plan on staying in Germany for the longer term. Around three quarters have found private accommodation and a similarly large share have already attended or are currently attending German language courses. Eighteen percent of the 18 to 64 year olds are employed; of the rest, over two thirds intend to start working immediately or within the next year. While almost all refugee children and adolescents of school age are attending a general or vocational school in Germany, only six out of ten children between three and six years old are attending daycare. To increase refugees' social participation and, in light of the high share of mothers among them, childcare options should be improved. This would facilitate participation in integration and language courses as well as the path to employment. In addition, it is crucial to quickly decide on the extension of Ukrainian refugees' right of residence, which is currently limited until March 2024, thus making their legal status more certain and planning possible.
Keywords: D31; I31; J31; 330; Ukrainian refugees; labor market participation; income; language acquisition; intention to stay; integration; health of children; child care